EVALUASI DAYA DUKUNG LAHAN UNTUK TANAMAN PANGAN PADA LAHAN PERKEBUNAN TEMBAKAU RAKYAT DI LERENG TIMUR GUNUNG SINDORO - Rahayu Rahayu (Faculty of Agriculture, Universitas Sebelas Maret, 2011)
Title : Evaluation of Land Capability for Food Plants at Rural Tobacco Area in East Part of Sindoro Mountain. This research was conduct at east part of Sindoro Mountain in Central Java with elevation around 1,000 – 2,000 m. Observation showed land degradation occurred in this location. This research was to know decreasing of land quality of tobacco area and the possibility of this area for food plants production as tobacco substitution. The steps of research were soil survey, laboratory analysis and plotting of land characteristics into food plants requirements. Results showed that the soils of area are Entisols and Andisols with slope of 8 to 30%. GIS analysis resulted in 5 land unit areas. Land suitability for tobacco is marginally suitable (S3) and not suitable (N) with limiting factors are precipitation, soil solum, pH H2O, C‐organic and slope. Land suitability for corn is marginally suitable (S3) and not suitable (N) with limiting factors are precipitation, soil solum, pH H2O, C‐organic and slope. Land suitability for cassava is not suitable (N) with limiting factors are soil solum and slopes. All of land unit areas have limiting factor for tobacco and food plants. Degradation of land resulted in decrease of quantity yield of tobacco.Keywords: food plants, land, soil degradation, tobacco